Controlling the Spatial Organization of Liquid Crystalline Nanoparticles by Composition of the Organic Grafting Layer. Issue 28 (2nd June 2015) - Wójcik, Michał M.; Olesińska, Magdalena; Sawczyk, Michał; Mieczkowski, Józef; Górecka, Ewa
Abstract Understanding how the spatial ordering of liquid crystalline nanoparticles can be controlled by different factors is of great importance in the further development of their photonic applications. In this paper, we report a new key parameter to control the mesogenic behavior of gold nanoparticles modified by rodlike thiols. An efficient method to control the spatial arrangement of hybrid nanoparticles in a condensed state is developed by changing the composition of the mesogenic grafting layer on the surface of the nanoparticles. The composition can be tuned by different conditions of the ligand exchange reaction. The thermal and optical behavior of the mesogenic and promesogenic ligands were investigated by using differential scanning calorimetry (DSC) and hot‐stage polarized optical microscopy. The chemical structure of the synthesized hybrid nanoparticles was characterized by 1H NMR spectroscopy, thermogravimetric analysis (TGA), XPS, and elemental analysis, whereas the superstructures were examined by small‐angle X‐ray diffraction (SAXSRD) analysis. Structural studies showed that the organic sublayer made of mesogenic ligands is denser with an increasing the average ligand number, thereby separating the nanoparticles in the liquid crystalline phases, which changes the parameters of these phases.